Senior citizens and over the counter drugs: challenges in rural India - Paul, Sherin Susan; Marconi, Sam; Gohain, Mrinmoy J; Bhatt, Arun Navin (International Journal of Research in Medical Sciences, 2016)
Background: The geriatric population is on a rise in India, which is accompanied by an increase in their health care needs. As they are prone to have multiple diseases simultaneously the tendency for over the counter (OTC) or non-prescription drugs is much higher among the elderly population. A thorough knowledge about the medication practices among elderly is indispensable since the chances for adverse drugs events; drug interactions etc. are higher among them. The primary objective of the present study was to measure the prevalence of over the counter drug usage among those aged 60 years or above residing in a rural block of North Tamilnadu, India. Methods: A community based cross sectional study was conducted among those aged 60 years or above using an interviewer administered questionnaire and data was collected from 100 consenting participants who were selected using multi stage sampling. Results: The prevalence of the usage of over the counter drugs among the elderly population was found to be 51% (95% CI 41.1-60.9). It was shown that the usage of OTC drugs was associated with higher socio economic status (p value 0.015) and literacy (p value 0.003). Conclusions: Further studies need to done to identify whether such high prevalence of OTC drug usage among elderly is a reflection of drug practices among general population and if proven otherwise should explore the various reasons for the same so that necessary measures can be implemented to alleviate the situation.